Chemo-Mechanical Extraction and Characterization of Sayote (Sechium edule) Fibers at Varying Fiber Maturity - Bandao-Antonio, Jennifer (Archīum Ateneo, 2023)
Cellulosic plant fibers are good reinforcing materials for composites because they are cheap, light weight, and exhibit good mechanical properties. The isolation of the crystalline portion exposes the stable hydrogen bond network that can form intermolecular bonding with other matrices, such as starch, polyvinyl alcohol and chitosan, among others. Sun-dried and undried sayote (Sechium edule) vines, of varying degrees of maturity, were subjected to uniform chemo-mechanical extraction procedures to obtain crystalline fibers. The chemo-mechanically extracted fibers were characterized using differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). DSC thermograms revealed that the sun-dried and mature sample exhibited the narrowest endotherm, indicating the presence of fewer amorphous structures. FTIR spectra showed that the numbers of functional groups present in the fiber samples decreased with increasing degree of maturity. SEM micrographs reveal that the mature portion of the sayote vine had more fibrous and orderly features, compared to the samples extracted from the younger and intermediate portions. Further, chemo-mechanical extraction and X-ray diffraction (XRD) analysis of fibers from mature, sun-dried sayote vines also revealed a relative crystallinity index of the extracted fiber of 65%. The fiber yield from the mature portion of the vine was 9%. Sayote (Sechium edule) vine can be a promising source of crystalline fibers for composite fabrication.